Psychological Portraits of the Mechanisms of Power: Subjective perceptions and deformed visions of reality in I Viceré by Federico De Roberto - Pagliaro, Annamaria (Spunti e Ricerche, 2016)
In this study I would like to focus on some aspects of I Viceré which make this novel an interesting document in which to assess De Roberto’s attempts to establish what I consider coherent poetics: the author’s growing sense of subjectivity drives him to delve more deeply into the psychology of his characters, exposing the breakdown of that particular kind of positivist thinking which recognises a solid, empirical reality that can be studied. Seen in the context of De Roberto’s other novels, I Viceré forms an integral part of his experimentation as he works towards the advancement of the modern novel and it should not be considered solely as the masterpiece which stands above the rest of his literary production.